Pengembangan Aplikasi Unggah Mandiri Repositori Karya Ilmiah Perpustakaan - wasilah; Riko Herwanto (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
The management of documentation for the publication of student writings at the IBI Darmajaya library has several problems. These problems include: the accumulation of files that must be inputted within a certain period of time, slow processing, and frequent data inconsistencies. Meanwhile, the publication of student scientific works is a valuable asset of the University and the academic community. So that scientific work that is managed and well documented is very much needed in a university.This study aims to build an independent upload repository for student scientific work publications. The research was conducted in several stages, namely: planning and needs analysis, design, system development and testing. The research produces outputs that facilitate the process of independent uploading of student papers. The independent upload process is carried out in several stages, starting from creating an account, uploading papers and validation from the editor.